Arbuscular Mycorrhizal Symbiosis Leads to Differential Regulation of Drought-Responsive Genes in Tissue-Specific Root Cells of Common Bean - Recchia, Gustavo H.; Konzen, Enéas R.; Cassieri, Fernanda; Caldas, Danielle G. G.; Tsai, Siu M. (Frontiers in Microbiology, 2018)
Arbuscular mycorrhizal fungi colonization in plants promotes both local and systemic changes in the gene expression profiles of the host that might be relevant for drought-stress perception and response. Drought-tolerant common bean plants (cv. BAT 477), colonized by a mixture of AMF (Glomus clarum, Acaulospora scrobiculata and Gigaspora rosea), were exposed to a water deprivation regime of 96 hours during pre-flowering. Root transcriptomes were accessed through RNA-Seq revealing a set of 9,965 transcripts with significant differential regulation in inoculated plants during a water deficit event, and 10,569 in non-inoculated. These data include 1,589 transcripts that are exclusively regulated by AMF-inoculation, and 2,313 under non-inoculation conditions. Relative gene expression analyses of nine aquaporin-related transcripts were performed in roots and leaves of plants harvested at initial stages of treatment. Significant shifts in gene expression were detected in AM water deficit treated roots, in relation to non-inoculated, between 48 and 72 hours. Leaves also showed significant mycorrhizal influence in gene expression, especially after 96 hours. Root cortical cells, harboring or not arbuscules, were collected from both inoculation treatments through a laser microdissection-based technique. This allowed the identification of transcripts, such as the aquaporin PvPIP2;3 and Glucan 1,3 β-Glucosidase, that are unique to arbuscule-containing cells. During the water deficit treatment, AMF colonization exerted a fine-tune regulation in the expression of genes in the host. That seemed to initiate in arbuscule-containing cells and, as the stressful condition persisted, propagated to the whole-plant through secondary signaling events. Collectively, these results demonstrate that arbuscular mycorrhization leads to shifts in common bean’s transcriptome that could potentially impact its adaptation capacity during water deficit events.